The Lost Island [compact disc, unabridged] : a Gideon Crew novel - Preston, Douglas J. (Preston, Douglas J. Gideon Crew novel., 2014)
Gideon Crew - brilliant scientist, master thief - is living on borrowed time. When his mysterious employer, Eli Glinn, gives him an eyebrow-raising mission, he has no reason to refuse. Gideon's task: steal a page from the priceless Book of Kells, now on display in New York City and protected by unbreakable security.